CD59 Expression in Skeletal Muscles and Its Role in Myasthenia Gravis. Issue 1 (17th January 2023) - Iwasa, Kazuo; Furukawa, Yutaka; Yoshikawa, Hiroaki; Yamada, Masahito; Ono, Kenjiro
Abstract : Background and Objectives: Complement regulatory proteins at the neuromuscular junction (NMJ) could offer protection against complement-mediated damage in myasthenia gravis (MG). However, there is limited information on their expression at the human NMJ. Thus, this study aimed at investigating the expression of the cluster of differentiation 59 (CD59) at the NMJ of human muscle specimens and demonstrating the overexpression of CD59 mRNA and protein in the muscles of patients with MG. Methods: In this observational study, muscle specimens from 16 patients with MG (9 and 7 patients with and without thymoma, respectively) and 6 nonmyopathy control patients were examined. Immunohistochemical stains, Western blot analysis, and quantitative real-time reverse transcription PCR were used to evaluate the CD59 expression. Results: A strong localized expression of CD59 was observed at the NMJ in both patients with and without MG. Moreover, the CD59/glyceraldehyde-3-phosphate dehydrogenase protein ratio in patients with MG was significantly higher than that in the nonmyopathy controls (MG; n = 16, median 0.16, interquartile range (IQR) 0.08–0.26 and nonmyopathy controls; n = 6, median 0.03, IQR 0.02–0.11, p = 0.01). The proportion of CD59 mRNA expression relative to AChR mRNA expression (ΔCtCD59/AChR ) was associated with the quantitative MG score, MG activities of daily living score, and MG of Foundation of America Clinical Classification ( r = 0.663, p = 0.01; r = 0.638, p = 0.014; and r = 0.715, p = 0.003, respectively). Discussion: CD59, which acts as a complement regulator, may protect the NMJ from complement attack. Our findings could provide a basis for further research that investigates the underlying pathogenesis in MG and the immunomodulating interactions of the muscle cells.